Análise de procedimentos de ensino do brincar de faz de conta para crianças com TEA: uma revisão sistemática - Natel, Jessika Mota (2022)
For people with ASD, play is a behavior that needs to be planned to be taught. Experimental studies, from the perspective of Behavior Analysis, were produced to analyze teaching procedures applied to this population. The objective of this study was to conduct a systematic review and analyze the variables involved in effective procedures for teaching pretend play to children with ASD, considering a taxonomy of play, presented in the literature in the area, concerning this behavior. For the search for applied studies, the databases PsycInfo, PubMed, and CAPES Periodicals were used, between the years 2011 and 2022. Twenty-one studies found were analyzed regarding the definition of make-believe play; the participants, the teaching procedures, the experimental design, the results that included the percentage of agreement between independent and integrity observers, in addition to the occurrence of measures of maintenance, generalization, and social validity. The main results indicate that researchers continue to define pretend play topographically or consider only antecedent events in their description; studies took place, in greater numbers, in structured environments and were conducted by experimenters, rather than people with whom the child was living, despite this behavior occurring in naturalistic environments. Another aspect analyzed was the generalization of the procedures, which, despite having been planned and measured, was conducted in one or two experimental conditions, without guaranteeing the learning of the behavior of pretend play in a generalized way (new people, environments, and objects ). It is presented a suggestion to update the taxonomy of pretend play for people with ASD with peer mediation, as the primary objective of this study